Yield and Quality of Irrigated Bermudagrass as a Function of Nitrogen Rate. (1st July 2014) - Sohm, Gregory; Thompson, Curtis; Assefa, Yared; Schlegel, Alan; Holman, John
Abstract : Bermudagrass [ Cynodon dactylon (L.) Pers.] is a perennial grass capable of producing a large amount of forage for either hay or grazing. Information on harvest frequency and rate of N for bermudagrass production is scarce for southwest Kansas. The objectives of this research were to determine economically and environmentally justified N rates for bermudagrass grown under supplemental irrigation (161–222 mm yr −1 ) and to determine annual harvest frequency. A field study was conducted from 2004 to 2007 near Rolla, KS, with five N rate treatments (0, 168, 336, 672, and 1344 kg N ha −1 ). On five harvest dates per year, biomass yield, feed quality, soil nutrient content, and soil pH were measured. Biomass yield was relatively high in the second, third, and fourth harvest dates out of five harvest dates within a year. In each of these five harvest dates, biomass yield increased with increasing N rates from 0 to 672 kg N ha −1 . A quadratic curve explained 80% of the variation for the relationship between total annual biomass yield of bermudagrass and N rate. The maximum average total annual dry matter production of about 18.5 Mg ha −1 was possible with 900 kg N ha −1 . The economic N rate that confers profit, however, varied from about 120 to 600 kg ha −1 depended on value of bermudagrass forage and variable cost of production. An increase in N rate from 0 to 672 kg N ha −1 also increased protein content and biomass feed quality without adversely affecting soil quality.